Proceedings of the 19th Annual SIGdial Meeting on Discourse and Dialogue 2018
DOI: 10.18653/v1/w18-5002
|View full text |Cite
|
Sign up to set email alerts
|

Changing the Level of Directness in Dialogue using Dialogue Vector Models and Recurrent Neural Networks

Abstract: In cooperative dialogues, identifying the intent of ones conversation partner and acting accordingly is of great importance. While this endeavour is facilitated by phrasing intentions as directly as possible, we can observe in human-human communication that a number of factors such as cultural norms and politeness may result in expressing one's intent indirectly. Therefore, in human-computer communication we have to anticipate the possibility of users being indirect and be prepared to interpret their actual me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Only a few recent studies have focused on pragmatic paraphrases to advance the understanding of users' intentions. Pragst and Ultes (2018) proposed a rule-based approach to automatically construct a corpus consisting of pairs of indirect and direct utterances. They demonstrated that the neural conversation model could accurately extract utterances with opposing directness.…”
Section: Related Workmentioning
confidence: 99%
“…Only a few recent studies have focused on pragmatic paraphrases to advance the understanding of users' intentions. Pragst and Ultes (2018) proposed a rule-based approach to automatically construct a corpus consisting of pairs of indirect and direct utterances. They demonstrated that the neural conversation model could accurately extract utterances with opposing directness.…”
Section: Related Workmentioning
confidence: 99%